Howes et al. Reply: - Howes, G; Cowley, S; Dorland, W; Hammett, G; Quataert, E; Schekochihin, A; Tatsuno, T (2008)
A Reply to the Comment by W.H. Matthaeus, S. Servidio, and P. Dmitruk. © 2008 The American Physical Society.